ANALISIS HASIL PENGUJIAN DCP DAN CPT SEBAGAI PENENTUAN PARAMETER KUAT GESER TANAH BANDARA SULTAN THAHA - Syahidus Syuhada; Puspa Ningrum; Fauzi Buldan Yaumun (LPPM Universitas Abdurrab, 2024)
Soil shear strength is an important component in infrastructure design. Many tests can be carried out to determine the shear strength of soil. The Cone Penetration Test (CPT) is a test commonly carried out to predict the shear strength of soil. Dynamic Cone Penetrometer (DCP) is often used to predict the value of soil shear strength in the form of the California Bearing Ratio (CBR) to determine the thickness of highway pavement. The shear strength of clay soil for building design purposes is usually expressed in undrained cohesion (cu) which can be obtained from CPT testing. With DCP and CPT tests carried out at the same location, the relationship between the shear strength parameters from these tests will be obtained. The results obtained were CBR = 0.2504 qc(kg/cm2) and cu (kPa) = 14.455 CBR (%). It is hoped that these results will be a rough estimate for road pavement design because DCP testing is limited in its use (only 1 m subgrade depth).